Kajian Teknis Alat Muat dan Alat Angkut untuk Meningkatkan Produksi pada Penambangan Andesit PT Arto Bangun Cemerlang di Kecamatan Tanjungsari, Kabupaten Bogor, Provinsi Jawa Barat - Shania Wulanda Sari; Zaenal; Sriyanti (Bandung Conference Series: Mining Engineering, 2023)
Abstract. PT Arto Bangun Cemerlang is a private mining company engaged in mining andesite minerals located in Garogol Village, Sirnarasa Village, Tanjungsari District, Bogor Regency, West Java Province. The total area is ± 50 Ha with a production target of 25,000 tons/month or 9,803.92 BCM/month, the production target has not been achieved. The products produced by this company consist of 3 products, namely split stone, stone ash and screening, where the marketing of these products is allocated to various areas in Jabodetabek, such as Serpong, Citeureup, Kasabalangka Karawaci, Karawang and Pulau Gadung. In mining activities there are several factors that influence the unachieved production of loading and hauling equipment. This is caused by the high tool cycle time, delay time and improper loading pattern. In this study, it discusses efforts to increase production in loading and conveyance equipment. The loading equipment for the Sany SY215 Excavator and the transport equipment use the Isuzu Giga Tronton Type FV 285 Dump Truck. The effort made is to reduce the cycle time of the loading equipment by changing the bottom loading pattern to top loading. Barrier time is the time for the loading and unloading equipment to not produce, the drag time for the conveyance and unloading equipment can be seen based on the work efficiency of the loading and unloading equipment. The work efficiency of the loading equipment is 62.31% and the work efficiency of the transportation equipment is 89.34%. Based on the results of work efficiency of loading and transport equipment, loading equipment has more waiting time compared to transportation equipment because of the high stand by time on transportation equipment compared to loading equipment. Based on actual production data on the Sany SY215 Excavator loading equipment of 9,475.2 BCM/month and the transportation equipment with 3 units of Isuzu Giga Tronton Type FV 285 Dump Trucks, namely 9,455.04 BCM/month. As for some improvements made such as the pattern of loading and reducing the cycle time (circulation time) of loading and hauling equipment. After the repairs were carried out, there was an increase in production of loading and conveyance equipment, where the production of loading and unloading equipment after repairs was 11,037.6 BCM/month and 11,022.48 BCM/month for conveyances. Abstrak. PT Arto Bangun Cemerlang merupakan perusahaan tambang swasta yang bergerak pada bidang pertambangan bahan galian andesit yang berlokasi di Kampung Garogol, Desa Sirnarasa, Kecamatan Tanjungsari, Kabupaten Bogor Provinsi Jawa Barat. Luas wilayah keseluruhan ± 50 Ha dengan target produksi 25.000 Ton/bulan atau 9.803,92 BCM/bulan, target produksi tersebut belum tercapai. Produk yang dihasilkan perusahaan ini terdiri dari 3 produk yaitu batu split, abu batu dan screening, dimana pemasaran dari produk tersebut dialokasikan ke berbagai daerah di Jabodetabek, seperti Serpong, Citeureup, Kasabalangka Karawaci, Karawang dan Pulau Gadung. Pada kegiatan penambangan adanya beberapa faktor yang berpengaruh terhadap ketidaktercapaian produksi alat muat dan angkut. Hal ini disebabkan oleh cycle time alat yang tinggi, waktu hambatan dan pola pemuatan yang kurang tepat. Pada penelitian ini membahas mengenai upaya untuk meningkatkan produksi pada alat muat dan alat angkut. Alat muat menggunakan Excavator Sany SY215 dan alat angkut menggunakan Dump Truck Isuzu Giga Tronton Tipe FV 285. Upaya yang dilakukan yaitu dengan menurunkan cycle time (waktu edar) pada alat muat dengan mengubah pola pemuatan bottom loading menjadi top loading dan penembahan jumlah penumpahan bucket pada alat angkut. Waktu hambatan merupakan waktu alat muat dan alat angkut tidak produksi, waktu hambatan pada alat angkut dan alat muat dapat dilihat berdasarkan efisiensi kerja alat muat dan alat angkut. Efisiensi kerja alat muat sebesar 62,31 % dan efisiensi kerja alat angkut sebesar 89,34%. Berdasarkan hasil efisiensi kerja alat muat dan alat angkut, alat muat lebih banyak waktu menunggu dibandingkan dengan alat angkut karena tingginya waktu stand by time pada alat muat dibandingkan dengan alat angkut. Berdasarkan data aktual produksi pada alat muat Excavator Sany SY215 sebesar 9.475,2 BCM/bulan dan alat angkut dengan 3 unit Dump Truck Isuzu Giga Tronton Tipe FV 285 yaitu sebesar 9.455,04 BCM/bulan. Adapun beberapa perbaikan yang dilakukan seperti pada pola pemuatan dan menurunkan cycle time (waktu edar) alat muat dan angkut. Setelah dilakukan perbaikan, terdapat peningkatan produksi pada alat muat dan alat angkut, dimana produksi alat muat setelah adanya perbaikan sebesar 11.037,6 BCM/bulan dan alat angkut 11.022,48 BCM/bulan.